A CONTINUOUS 5300-YR HOLOCENE CRYPTOTEPHROSTRATIGRAPHIC RECORD FROM NORTHERN NEW ZEALAND AND IMPLICATIONS FOR TEPHROCHRONOLOGY AND VOLCANIC HAZARD ASSESSMENT - Gehrels M.J.; Hazell Z.J.; Newnham R.M.; Lowe D.J. (My University, 2006)
A continuous ~ 5280 calendar (cal.) yr long cryptotephrostratigraphic record of a peat core from northern New Zealand demonstrates that cryptotephra studies can enhance conventional tephra records by extending the known distribution of ash fall and enabling re-assessment of volcanic hazards. A systematic sampling strategy was used to locate peaks in glass-shard concentrations and to determine loci of individual geochemical populations, and a palynological method involving spiking samples with Lycopodium spores was adapted to facilitate accurate counting of glass-shard concentrations. Using glass-shard major element compositions, and a core chronology based on eight AMS 14C ages and two visible macroscopic tephra layers, Taupo Tephra (Unit Y) (1688-1748 cal. BP) and Tuhua Tephra (6800-7230 cal. BP) (2σ-age ranges), four cryptotephras were correlated with known eruptions: Whakaipo (Unit V) (2743-2782 cal. BP), Stent (Unit Q) (4240-4510 cal. BP), and Unit K (4970-5290 cal. BP), erupted from Taupo Volcanic Centre, and Whakatane Tephra (5470-5600 cal. BP) erupted from Okataina Volcanic Centre. Mixed glass populations were found in the core, most likely an artefact of post-depositional remobilization of shards vertically (both up and down) in the peat or on its surface by wind, or a result of closely spaced eruption events, or a combination of these. A secondary glass population identified within the macroscopic Taupo Tephra was tentatively attributed to either an earlier phase within that eruption or to mixing with a slightly older Taupo-derived eruptive or (less likely) a currently unknown Okataina-derived eruptive. These results indicate that, in the absence of continuous cryptotephrostratigraphic analysis, a peak in shard concentrations may not in itself be indicative of the 'true' stratigraphic (ie, isochronous) level of a tephra layer. For cryptotephra studies of peat cores, we recommend (1) using a detailed sampling strategy for the analysis of distal tephra-derived glass to detect and account for any mixed populations and possible vertical spread of glass shards through the peat, and (2) analysing more shards from larger samples to help 'capture' sparsely represented cryptic andesitic tephra deposits. © 2006 Edward Arnold (Publishers) Ltd.
Keywords: 14C DATING; CRYPTOTEPHRA; GLASS COUNTS; HOLOCENE; ISOCHRONS; KOPOUATAI BOG; NEW ZEALAND; NORTH ISLAND; PEAT CORES; TEPHRA; TEPHROCHRONOLOGY; VOLCANIC HAZARDS; Cenozoic::Quaternary::Holocene; Кайнозой::Четвертичная::Голоцен